Pro .NET 2.0 Windows Forms and Custom Controls in C# - MacDonald, Matthew (Apress, 2012)
Four years after the .NET Framework first hit the programming scene, smart client applications still refuse to die. This is significant because when .NET first appeared, all too many people assumed it was about to usher in a new world of Web-only programming. In fact, for a short time Microsoft’s own Web site described the .NET Framework in a single sentence as a “platform for building Web services and Web applications”—ignoring the Windows technology that made the company famous. Now that the dust has settled, it’s clear that Web and Windows applications aren’t locked in the final rounds of a life-or-death battle. Instead, both technologies are flourishing. And not only are both technologies gaining strength, but they’re also stealing some of each other’s best features. For example, the latest release of .NET gives Web developers rich controls like menus and trees that were previously the exclusive domain of Windows coders (or Web-heads who weren’t afraid to write a mess of hardcore client-side JavaScript). On the other hand, Windows applications are gaining easy Web-based deployment, more-flexible layout options, and the ability to display HTML. All of these innovations point to many productive years ahead for Web and Windows developers alike.